THE INFLUENCE OF SERVICE QUALITY AND SATISFACTION ON CUSTOMER LOYALTY - Al Fahrezi, Muhammad Farid; Muniroh, Leny; Kuraesin, Ecin; Megawati, Dewi (Manager : Jurnal Ilmu Manajemen, 2025)
This research was conducted with the aim of knowing the effect of service quality and satisfaction on customer loyalty at Warkop Berkah Big’s Family. The sample of the research were the customers of Warkop Berkah Big’s Family, as many as 100 respondents, and using purposive sampling with descriptive analys tehnique, validation, reliability, multiple liniearregression and hypotesa test. The results showed that quality service has a tcount value of 3.646 > ttable 1.660 which has a positive effect on customer’s loyalty. Satisfaction has a value of tcount 8.592 > ttable 1.660 which has a positive effect on customer’s loyalty. Quality service and satisfaction have value Fcount 79.090 > Ftable 3.089 a positive effect on customer’s loyalty. This the hypothesis is H1 and H2 accepted. So it can be concluded that quality service and satisfaction effect customer’s loyalty in warkop berkah big’s family. So H3 is accepted